Management Of Portfolio Of Mutual Funds:Developing a model for allocation of funds in portfolios of mutual Funds by Indian Investors based on the risk-need analysis - Bhandari, Punya (2010)
This dissertation focuses on developing a model to for asset allocation in a portfolio of mutual funds for an average Indian Investor. When an investor sets out to invest or buy mutual fund units, the investor may find that there are a number of mutual funds available. Which mutual fund to invest and how much to invest is a big question mark in front of the investor.